2019
DOI: 10.1007/s11433-019-9451-3
|View full text |Cite
|
Sign up to set email alerts
|

Weak-force sensing with squeezed optomechanics

Abstract: We investigate quantum-squeezing-enhanced weak-force sensing via a nonlinear optomechanical resonator containing a movable mechanical mirror and an optical parametric amplifier (OPA). Herein, we determined that tuning the OPA parameters can considerably suppress quantum noise and substantially enhance force sensitivity, enabling the device to extensively surpass the standard quantum limit. This indicates that under realistic experimental conditions, we can achieve ultrahighprecision quantum force sensing by ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 102 publications
0
29
0
Order By: Relevance
“…Hamiltonian of the optomechanical system (OMS), Hamiltonian of the OPA [37], Hamiltonian of the atomic ensemble, and the Hamiltonian of the laser driving field [42] can be written as the following expressions: and…”
Section: Hybrid Optomechanical System and Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Hamiltonian of the optomechanical system (OMS), Hamiltonian of the OPA [37], Hamiltonian of the atomic ensemble, and the Hamiltonian of the laser driving field [42] can be written as the following expressions: and…”
Section: Hybrid Optomechanical System and Modelmentioning
confidence: 99%
“…At the same time, the low-frequency sensitivity was remained unchanged. On the other hand, as mentioned in section I, Zhao et al [37] investigated weak-force sensing in a squeezed cavity and theoretically showed that the SQL could be suppressed at frequencies below the mechanical resonance; however, the back-action noise remained unchanged in the system.…”
Section: Force Sensing and Cqncmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 53 ] Optical forces give rise to the interaction between light and mechanical resonators, [ 54 ] which has recently formed a booming research field named optomechanics, with huge potential for quantum information processing, [ 55 ] as well as high‐precision sensing and measurement. [ 56–60 ]…”
Section: Introductionmentioning
confidence: 99%